Adoption Analysis of Hybrid Rice Development in Indonesia - Satoto Satoto; Yuni Widyastuti; Nita Kartina; Bayu Pramono Wibowo (Iptek Tanaman Pangan, 2017)
The current rice productivity tends to be stagnant and even falling, due to the biotic and abiotic stresses and is affected by global climate changes. An alternative to solve the problem is to use the effect of heterosis through hybrid rice technology. China had pioneered in developing hybrid rice and farmers had been successfully adopting widely hybrid rice variety. Indonesia is still lagging behind in developing hybrid rice technology where the rate of hybrid rice diffusion in farmers fields tend to be slow. Around 4.92% of the total rice area is currently planted with hybrid rice. It is necessary to analyze factors that cause the low level of hybrid rice adoption in Indonesia. Factors affecting farmers’ responses to hybrid rice included socio economic factor and farmers’ profiles, hybrid rice productivity, degree of varietal resistance to pests and deseases, grain quality, cultivation technique, cost of production, selling price of grain and availability of information. This paper identified challenges and obtacles in hybrid rice development, analyzed factors that influence the adoption rate, and to recommend policies that encourage the development of hybrid rice varieties in Indonesia.